2022
DOI: 10.3389/fneur.2022.855664
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between subjective and objective memory change after epilepsy surgery: Relation with seizure outcome and depressive symptoms

Abstract: Complaints pertaining to memory functioning are among the most often reported cognitive symptoms in patients with epilepsy. However, research suggests a considerable mismatch between patients' perception of memory functioning and the objective performance as measured with standardized neuropsychological tests. Depressive mood might be an important factor in explaining this discrepancy, though other variables have also occasionally been reported as relevant. There are mixed results as to which role these factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As we focused on subjective psychological data, we did not include objective measures of cognition. Subjective and objective cognition may differ, 48 so that it would be intriguing to investigate the differential impact of both on patients' decisions in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…As we focused on subjective psychological data, we did not include objective measures of cognition. Subjective and objective cognition may differ, 48 so that it would be intriguing to investigate the differential impact of both on patients' decisions in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study, depressive symptoms were only linked to executive functions, whereas based on the aforementioned rationales, attentional and memory impairment may also be expected. However, in PWE, some studies found correlations between depressive symptoms and different cognitive functions, 15,19,30 whereas other did not 22,59–61 . Thus, it seems necessary to differentiate between groups of PWE (e.g., presurgical vs. outpatient samples, localization of the brain lesion 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…We examined concordance of SCI and OCI by comparing subjective reports and objective performance 16,30 . SCI scores were classified based on the same recommendations as the objective performance 34 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations